Cascade JT systems with single-component refrigerants for hydrogen liquefaction. (January 2022) - Chang, Ho-Myung; Park, Min Gyun
Highlights: Hydrogen liquefaction systems without cryogenic expander are investigated. Cascade JT systems with single-component refrigerants are suitable for large-scale liquefaction. Modified Linde-Hampson systems with a variety of pre-cooling cycles are optimized. A reasonably high efficiency can be achieved with the optimized cascade JT systems. Abstract: A thermodynamic study is carried out for hydrogen liquefaction with cascade Joule-Thomson (JT) systems, which do not require any expansion machines. Since there is no moving part at cryogenic temperatures, the cascade JT systems have a potential advantage of high reliability and easy scale-up of liquefaction capacity, as demonstrated in the full-scale LNG plants under operation. A variety of combinations for pre-cooling JT cycles with single-component refrigerants (including neon, nitrogen, argon, oxygen, hydrocarbons, and ammonia) are investigated to estimate the figure of merit (FOM) as a performance index of liquefaction. In every JT cycle, the pressure levels are optimized to maximize the FOM with a process simulator (Aspen HYSYS) and real properties of working fluids (NIST REFPROP). It is rigorously shown that the cascade JT systems can achieve a reasonably high FOM, if the irreversibility below 77 K is effectively reduced. A few suitable cascade systems for large-capacity hydrogen liquefaction are identified, and the details of optimized cycles are presented.